Redução eletrocatalítica de CO2 e detecção colorimétrica de Zn2+ promovidas por um novo complexo de Re(I) contendo a 4-etil-3-tiossemicarbazida - Souza, Breno Luiz de (2018)
This work reports the preparation of a novel Re (I) tricarbonyl complex with a 4-ethyl-3-thiosemicarbazide derivative. The novel (Z)-N-ethyl-2-(6-oxo-1,10-phenanthrolin-5(6H)-ylidene) hydrazinecarbutyrate (phet) was obtained for this purpose. The complex fac-[ReCl(CO)3(phet)] and the free ligand phet were characterized by hydrogen nuclear magnetic resonance (1H-NMR) spectroscopy and by absorption spectra in the UV-vis region, which were compared with theoretical simulations obtained (TD-DFT). It was possible to attribute the transitions in the visible region of the spectrum to IL, MLCT and LLCT transitions. The luminescence data showed a radioactive decay associated with excited states centered on the phet ligand. Electrochemical characterization of the ligand and the complex reveals a redox pair associated to the carbonyl group bound to the phenanthroline rings, as well as redox processes related to the thiosemicarbazone substituent. The proton dissociation constants of the ground (pβ) and excited (pβ *) states of the new complex were also determined. The values of pβ = 9.9 and pβ * = 11.5 show the proton loss is facilitated in the ground state, i.e. the specie is a weaker Bronstead acid in the excited state. Due to the various free coordination sites of thiosemicarbazone, colorimetric tests with ZnCl2 were performed and accompanied by changes in absorption spectra in the UV-vis region which showed a 1:1 (Zn2+:Complex) molar ratio interaction. The high redox activity of the complex also allowed its application as electrocatalyst for CO2 reduction. The heterogeneous tests with the electropolymerization of the compound on the vitreous carbon electrode surface showed catalytic reduction currents c.a. 5.5 times higher than those for the homogeneous tests. These results suggests the potential of the new complex to act as a catalyst in the CO2 valorization.